Dekonstruksi Stereotip Gender Dalam Iklan “Kebahagiaan Kecil” Gopay Indonesia - Octaviana, Rizka; Mustiawan, Mustiawan; Setiawati, Titin (PRoMEDIA, 2024)
AbstractThis study aims to analyze the deconstruction of gender stereotypes in GoPay Indonesia's "Kebahagiaan Kecil" advertisement, which depicts the role of fathers in domestic tasks. Using a qualitative approach and content analysis method, this study focuses on six important scenes showing a father cooking, taking care of children, and cleaning the house. The results show that this advertisement has the potential to challenge patriarchal norms by depicting more equal gender roles. However, the strong elements of masculinity in this advertisement indicate inconsistencies in breaking down gender stereotypes. Furthermore, the study reveals that the commodification of gender equality issues in advertisements is used as a capitalist practice to attract audience attention. Although this advertisement discusses equal domestic roles, its implementation in society is still symbolic and does not reflect structural changes. This study contributes to the field of communication science by showing the role of media in shaping and changing social meanings, especially in gender representation. Further research is recommended to examine the long-term impact of gender representation in the media and audience responses to changes in gender roles displayed.Keywords: Gender Deconstruction, Advertising, Gender Stereotypes.AbstraksiPenelitian ini bertujuan untuk menganalisis perubahan stereotip gender dalam iklan "Kebahagiaan Kecil" GoPay Indonesia, yang menggambarkan peran ayah dalam tugas domestik. Penelitian ini menggunakan pendekatan kualitatif dan metode analisis isi, dengan memfokuskan pada enam adegan penting yang menunjukkan peran ayah adalam urusan domestic keluarga. Hasilnya menunjukkan bahwa iklan ini berpotensi menantang norma patriarki dengan menggambarkan peran gender yang lebih setara. Namun, elemen maskulinitas yang kuat dalam iklan ini menunjukkan adanya ketidakkonsistenan dalam meruntuhkan stereotip gender. Lebih lanjut, penelitian mengungkapkan bahwa komodifikasi isu kesetaraan gender dalam iklan digunakan sebagai praktek kapitalis dalam menarik perhatian audiens. Meski iklan ini membuka perbincangan tentang kesetaraan peran domestik, implementasinya di masyarakat masih bersifat simbolis dan belum mencerminkan perubahan struktural. Penelitian ini memberikan kontribusi pada bidang ilmu komunikasi dengan menunjukkan peran media dalam membentuk dan mengubah makna sosial, khususnya dalam menggambarkan gender. Penelitian selanjutnya disarankan untuk meneliti dampak jangka panjang menggambarkan gender dalam media dan respons audiens terhadap perubahan peran gender yang ditampilkan.Kata Kunci: Dekonstruksi Gender, Iklan, Stereotip Gender.